A critical analysis of decision support systems research revisited: The rise of design science - Arnott, D.; Pervan, Graham (2016)
© Association for Information Technology Trust 2016.Decision support systems (DSS) is the area of the information systems (IS) discipline that is focused on supporting and improving managerial decision making. In 2005 the Journal of Information Technology (JIT) published our paper that critically analyzed DSS research from 1990 to 2003 (Arnott and Pervan, 2005). That paper used bibliometric content analysis as its method and analyzed 1020 articles in 14 journals. The analysis illuminated a vibrant and important part of IS research. Personal DSS and group support systems (GSS) dominated DSS research and two-thirds of DSS research was empirical, a higher proportion than general IS research. Interpretive DSS research was growing from a low base while design-science research (DSR) and laboratory experiments were major research categories. Unfortunately, it was found that DSS research to 2003 was relatively poorly founded on judgment and decision-making theory and faced what was described as ‘a crisis of relevance’.